EARLY GASTRIC CANCER: THE MODERN OPINION - S. S. Pirogov; V. V. Sokolov; M. M. Belyakov; A. D. Kaprin (Сибирский онкологический журнал)
The review presents the clinical and morphological characteristics of early gastric cancer. According to the most recent concepts, early gastric cancer is considered as endoscopically resectable cancer with good prognosis. Currently, early gastric cancer is defined as non-invasive high-grade intraepithelial neoplasia (severe dysplasia) and well-differentiated adenocarcinoma with intramucosal (T1a) and/or minor submucosal (T1b1) invasion as well as poorly cohesive carcinoma, including signet-ring cell carcinoma, confined to the gastric mucosa (≤ 3 cm) without ulceration. Most authors consider that early gastric cancer should be characterized by the absence of regional lymph nodes (N0) and distant metastasis (M0). Early gastric cancer should be classified according to the macroscopic criteria proposed by the Japanese Society of Gastroenterological Endoscopy or the revised version of the Paris classification of superficial neoplastic lesions in the digestive tract as well as according to the World Health Organization classification and the recommendations of the Japanese Gastric Cancer Association. It is important to evaluate lymphovascular invasion in all early gastric cancer cases because of high risk of local metastases. Moreover, cases with mixed-type early gastric cancer (differentiated and undifferentiated components) need to be carefully examined, as they are high-metastatic potential lesions. The review considers predictive criteria for assessing the risk of regional metastasis in early gastric cancer. Cases of hereditary diffuse gastric cancer caused by CDHI gene mutations have been also analyzed. A literature review have allowed us to give recommendations on the risk stratification and the choice of an adequate treatment in patients with early gastric cancer